Answer:
1+1= 11
1Step-by-step explanation:
I might be wrong so if i am right pls give me a thanks
Answer:
Was there suppose to be a attached image?
Hello from MrBillDoesMath!
Answer:
No
Discussion:
If the functions are inverses, then f(g(x)) = x for appropriate x. Consider x = 1.
g(1) = 1/ (5(1) + 1) = 1/6
f(g(1)) = f (1/6) = 5(1/6) + 1/ (1/6) = 5/6 + 6 = 6 5/6 <> 1
Conclusion: f(g(1)) <> 1 so the functions are not inverses
Thank you,
MrB
Answer:
![no \: solution](https://tex.z-dn.net/?f=no%20%5C%3A%20solution)
Step-by-step explanation:
1) Expand
![6x - 36 - 5x + 35 = x + 6](https://tex.z-dn.net/?f=6x%20-%2036%20-%205x%20%2B%2035%20%3D%20x%20%2B%206)
2) Simplify 6x - 36 - 5x + 35 to x - 1.
![x - 1 = x + 6](https://tex.z-dn.net/?f=x%20-%201%20%3D%20x%20%2B%206)
3) Cancle x on both sides.
![- 1 = 6](https://tex.z-dn.net/?f=%20-%201%20%3D%206)
4) Since −1 = 6 is false, there is no solution.
No Solution
Hence, this equation have no solution.